(untitled) (Academic Journal of Internal Affairs, 2023)
The Civil Guard is a success story of the 1989-1990 change of regime. It was established when the most active part of society had had enough of the increasing levels of crime, the decline of the people’s sense of security and the underachieving law enforcement and judiciary. During the change of regime, against an increased wave of criminality stood a weakened police force that was prepared for handling less crime, in search of itself – its identity –, therefore unable to provide an acceptable level of security. Naturally, as people’s movements, the locals established Self-defense Groups, but separately from each other, without any preparation or cooperation. The first, founding president of the organization was Sándor Kopácsi, chief commissioner of the Hungarian Police in 1956, who gave sufficient guarantee that the Civil Guard would not be involved in politics and aim only at crime prevention. Aim: The civil guards were volunteers, dedicated to their neighborhood, who spent not only their time for the good of the public, but also financed themselves. In the middle of the 1990s, serious differences emerged regarding the future development of the Civil Guard. The new leaders wanted to enter politics, gain positions in local governments. They also demanded more and more powers (the right to conduct identity checks and means of coercion); basically, militant efforts rose that festered into personal feuds. It all ended in 1997 in a thorough change among the top-level officers. The winners of the 2010 Public Security Concept were the country and the Civil Guard. With the pertinent piece of legislation enacted, the Civil Guard was turned into a non-profit organization and politically aligned non-governmental organizations were barred from crime prevention in public, open places as their appearance were only a source of disturbance. Methodology: The Act on the Civil Guard created the necessities for the long-term operation of the organization, set up its legal framework and laid the groundwork for its development. Findings: After the law was enacted, the Civil Guard started to develop quite visibly. The civil guards participated in crime prevention with unbelievable vigor. In the last decade, the Civil Guard has started to specialize. Separate sections were dedicated to traffic, the youth, mounted patrol, the protection of the environment, as well as the state border. The presidency of the Civil Guard established the Border Protection Section in the autumn of 2016 which was joined by 95 associations and 2050 civil guards in the border areas. Value: The Government of Hungary in a decree, with the preliminary consent of the Civil Guard, asked the organization to – permanently, predictably and in a coordinated manner – participate in the protection on the Serbian-Hungarian border in Csongrád-Csanád and Bács-Kiskun counties. As per the requirement of the Hungarian Police, 82 civil guards served on the border every day in 2022. During their service, the Civil Guard arrested or contributed to the arrest of 15,858 people committing illegal border crossing. The Civil Guard associations of Ásotthalom, Mórahalom, Röszke and those of the counties are exemplary. The civil guards serve on the southern borders of our country as true everyday heroes.